In vitro and in silico assessment of probiotic and functional properties of Bacillus subtilis DE111® - Mazhar, Shahneela; Khokhlova, Ekaterina; Colom, Joan; Simon, Annie; Deaton, John; Rea, Kieran (Frontiers in Microbiology, 2023)
Bacillus subtilis DE111® is a safe, well-tolerated commercially available spore-forming probiotic that has been clinically shown to support a healthy gut microbiome, and to promote digestive and immune health in both adults and children. Recently it was shown that this spore-forming probiotic was capable of germinating in the gastrointestinal tract as early as 3 hours after ingestion. However, a better understanding of the mechanisms involved in the efficacy of DE111® is required. Therefore, the present investigation was undertaken to elucidate the functional properties of DE111® through employing a combination of in vitro functional assays and genome analysis. DE111® genome mining revealed the presence of several genes encoding acid and stress tolerance mechanisms in addition to adhesion proteins required to survive and colonize harsh gastrointestinal environment including multi subunit ATPases, arginine deiminase (ADI) pathway genes (argBDR), stress (GroES/GroEL and DnaK/DnaJ) and extracellular polymeric substances (EPS) biosynthesis genes (pgsBCA). DE111® harbors several genes encoding enzymes involved in the metabolism of dietary molecules (protease, lipases, and carbohyrolases), antioxidant activity and genes associated with the synthesis of several B-vitamins (thiamine, riboflavin, pyridoxin, biotin, folate), vitamin K2 (menaquinone) and seven amino acids including five essential amino acids (threonine, tryptophan, methionine, leucine, and lysine). Furthermore, a combined in silico analysis of bacteriocin producing genes with in vitro analysis highlighted a broad antagonistic activity of DE111® towards numerous urinary tractk, intestinal, and skin pathogens. Enzymatic activities included proteases, peptidases, esterase’s, and carbohydrate metabolism coupled with metabolomic analysis of DE111® fermented ultra-high temperature milk, revealed a high release of amino acids and beneficial short chain fatty acids (SCFAs). Together, this study demonstrates the genetic and phenotypic ability of DE111® for surviving harsh gastric transit and conferring health benefits to the host, in particular its efficacy in the metabolism of dietary molecules, and its potential to generate beneficial SCFAs, casein-derived bioactive peptides, as well as its high antioxidant and antimicrobial potential. Thus, supporting the use of DE111® as a nutrient supplement and its pottential use in the preparation of functional foods.